Immunization with a novel mRNA vaccine, TGGT1_216200 mRNA-LNP, prolongs survival time in BALB/c mice against acute toxoplasmosis - Zhang, Yizhuo; Li, Dan; Shen, Yu; Li, Shiyu; Lu, Shaohong; Zheng, Bin (Frontiers in Immunology, 2023)
Toxoplasma gondii, a specialized intracellular parasite, causes a widespread zoonotic disease and is a severe threat to social and economic development. There is a lack of effective drugs and vaccines against T. gondii infection. Recently, mRNA vaccines have been rapidly developed, and their packaging materials and technologies are well established. In this study, TGGT1_216200 (TG_200), a novel molecule from T. gondii, was identified using bioinformatic screening analysis. TG_200 was purified and encapsulated with a lipid nanoparticle (LNP) to produce the TG_200 mRNA-LNP vaccine. The immune protection provided by the new vaccine and its mechanisms after immunizing BABL/C mice via intramuscular injection were investigated. There was a strong immune response when mice were vaccinated with TG_200 mRNA-LNP. Elevated levels of anti-T. gondii-specific immunoglobulin G (IgG), and a higher IgG2a-to-IgG1 ratio was observed. The levels of interleukin 12 (IL-12), interferon-γ (IFN-γ), IL-4, and IL-10 were also elevated. The result showed that the vaccine induced a mixture of Th1 and Th2 cells, and Th1-dominated humoral immune response. Significantly increased antigen-specific splenocyte proliferation was induced by TG_200 mRNA-LNP immunization. The vaccine could also induce T. gondii-specific cytotoxic T lymphocytes (CTLs). The expression levels of interferon regulatory factor 8 (IRF8), T-Box 21 (T-bet), and nuclear factor kappa B (NF-κB) were significantly elevated after TG_200 mRNA-LNP immunization. The levels of CD83, CD86, MHC-I, MHC-Ⅱ, CD8, and CD4 molecules were also higher. The results indicated that TG_200 mRNA-LNP produced specific cellular and humoral immune responses. Most importantly, TG_200 mRNA-LNP immunized mice survived significantly longer (19.27 ± 3.438 days) than the control mice, which died within eight days after T. gondii challenge (P < 0.001). The protective effect of adoptive transfer was also assessed, and mice receiving serum and splenocytes from mice immunized with TG_200 mRNA-LNP showed improved survival rates of 9.70 ± 1.64 days and, 13.40 ± 2.32 days, respectively (P < 0.001). The results suggested that TG_200 mRNA-LNP is a safe and promising vaccine against T. gondii infection.